Pertanggungjawaban BPN Dan PPAT Terhadap Sertifikat Hak Milik Atas Tanah Akibat Sengketa Kepemilikan Hak Atas Tanah - Irawaty Aliya Pakaya; Mutia Cherawaty Thalib; Taufiq Zulfikar Sarson (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This article analyzes the responsibilities of the National Land Agency (BPN) and Land Deed Officials (PPAT) regarding title certificates for land subject to ownership disputes. The research method used is normative legal research with statutory, conceptual and case approaches. Based on the case studied, the legal owner of the land, Ansar Lause, filed a lawsuit because the land certificate was changed to be in the name of Ratna Lause illegally. After the trial process, the court decided to partially grant Ansar Lause's lawsuit and stated that the certificate in the name of Afandi Surya Ningrat had no binding legal force. The research results show that the legal impact on BPN of canceling property rights certificates by the court based on a decision is that BPN can be subject to administrative sanctions in the form of a written warning, temporary dismissal, honorable dismissal, or dishonorable dismissal; and a Notary/PPAT who is subject to the cancellation of a certificate of ownership by a court based on a decision is that the Notary/PPAT may be subject to administrative sanctions in the form of a written warning, temporary dismissal, honorable dismissal, or dishonorable dismissal; and the form of BPN accountability, this responsibility can be in the form of administrative improvements, review of the certificate issuance process, as well as protection of the rights of parties who suffer losses due to administrative errors and PPAT/Notary for property rights certificates that have been canceled by the court. PPAT/Notary can be held civilly responsible. , criminal, and administrative.